An investigation into the pre-service training of secondary school mathematics teachers at colleges of education administered by the House of Representatives - Hendricks, Mogamat Armien (Rhodes University, Faculty of Education, Department of Education, 1989)
This study involves an investigatioh into the nature and effectiveness of the pre-service training, where provided, of secondary school Mathematics teachers at the 11 colleges of education administered by the House of Representatives in the Republic of South Africa. The purpose of this study is to determine whether the HDE (Secondary) course offered at some of the aforementioned colleges of education is justified, In spite of the fact that it contravenes the requirements of the Education Act, No. 73 of 1969. Three different questionnaires were designed and during 1986 were sent to heads of Mathematics departments at the aforementioned colleges of education , to Mathematics teacher educators at these colleges and to beginning secondary school Mathematics teachers, teaching at schools administered by the House of Representatives in the Eastern Cape and Natal. The findings of this study show that the secondary course for Mathematics teachers is only offered at 5 of the 11 colleges of education and only a small percentage of students take this course. During 1986 most of the Mathematics teacher educators at the colleges of education were not suitably qualified. The study also shows that the Mathematics curriculum for the training of secondary school teachers is inadequate and a revision thereof is thus recommended. An obvious conclusion drawn from the findings is that the training of secondary school Mathematics teachers at these colleges of education is still in an early stage of development. One of the main recommendations of this study is that the training of secondary school Mathematics teachers at colleges of education administered by the House of Representatives should be terminated , in view of its ineffectiveness and In accordance with Education Act , No . 73 of 1969. On the other hand, in case this is not possible, suggestions are also made for the improvement of the pre-service training of secondary school mathematics teachers at these colleges of education.
Keywords: Mathematics teachers -- Training of -- South Africa; Mathematics -- Study and teaching (Higher) -- South Africa; Colored people (South Africa) -- Education; Colored people (South Africa) -- Education (Secondary)